Phonoholism as a Sign of 'Always on' Generation - Research Report - Andrzej Łuczyński; Lidia Pietruszka (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article presents research on the risk of phonoholism occurring among high school students. Strong attachment to a cell phone, for many students, can be an indicator of serious problems. Thanks to utilizing in research the diagnostic survey method, 450 high school students, from all over Poland, could express their opinions on the dangers associated with using a mobile phone. Their opinions were analysed in terms of the ability to use a smartphone rationally, including the possibility of temporarily quitting or limiting the use of a mobile phone. Survey data analysis showed that students do not notice any negative effects of using a cell phone, at the same time they declare that functioning without a phone would be very difficult or even impossible for them. The results suggest that such risk do exist in some extent, for this reason, more emphasis should be placed on preventive measures that can help effectively to protect students against phonoholism.